Strategi Adaptasi Biro Tour And Travel Dalam Menghadapi Pendemi Covid-19 (Studi Kasus Pada Perusahaan Tour And Travel Haji dan Umrah PT AQM Kota Bengkulu) - Melati Oktavia utami; Miti Yarmunida; Yunida Een Fryanti (UNIVED Press, 2022)
This study aims to determine the adaptation strategy of tour and travel bureaus in dealing with the COVID-19 pandemic. This study uses a descriptive qualitative approach with the object of AQM research in Bengkulu City with Mr. Heru Putra Perdana A.Md. as General Supervisor/IT. Data collection techniques used are interviews, observation and documentation. data analysis technique is descriptive qualitative by collecting, managing, analyzing and presenting data. The results of this study the authors conclude that Covid-19 has greatly impacted the Umrah Travel Organizer (PPIU) at PT. The Quba Mandiri Award for Bengkulu City. the adaptation strategy of the tour and travel bureau in dealing with the covid-19 pandemic, it can be concluded that the adaptation strategy used is by applying an adaptive strategy (adjustment strategy), an adaptive strategy of prospectors and defenders types, namely making adjustments to current conditions, innovations made by PT . Anugerah Quba Mandiri City of Bengkulu with the formation of a 3s team, recruiting as many employees as possible, the tamrah system (umrah savings), and booking a sit down deposit of 5 million. To restore the company's income, opening a new business, a raudoh figure is a branch of AQM such as Muslim clothes, Umrah gifts, zam-zam water, dates, etc. apply Umrah savings in cooperation with the appointed bank. People can save at any time while waiting for confirmation of departure. This strategy led to innovations aimed at attracting public interest and keeping the company afloat.